Operational site selection for disaster management bases in Tehran, Iran - SAYYED ALI , ALAVI; ABOLFAZL , MESHKINI; MOHAMMAD , EBRAHIMI (MAUSAM, 2020)
Natural disasters play a main role in human life. It should be taken into consideration that it is impossible to predict these disasters from happening, but preparation for a good response for these disasters can be a good solution to decrease post-damage casualties in the cities. Herein, Disaster Management Bases in terms of prevention, preparation and dealing with the crisis play a key role, especially in Tehran and in times of natural disasters. There is no doubt that a high level and efficient function of these bases has a striking correlation with the way they are located in both an urban and regional level in a way that in addition to providing security of the bases against disasters, based on the service area they could be able to provide good services for the areas of crisis. This paper tries to use Multi Criteria Decision Making (MCDM) techniques and spatial analysis method in order to assess the effectiveness of these bases. Based on assessments Disaster Management Bases have spontaneously distributed in Tehran and have located in inappropriate places. Thus using MCDM with GIS analysis, the best locations in case study area was proposed.